Preparation of nanobubbles carrying androgen receptor siRNA and their inhibitory effects on androgen-independent prostate cancer when combined with ultrasonic irradiation. - Luofu Wang; Miao Zhang; Kaibin Tan; Yanli Guo; Haipeng Tong; Xiaozhou Fan; Kejing Fang; Rui Li (PLoS ONE)
Objective The objective of this study was to investigate nanobubbles carrying androgen receptor (AR) siRNA and their in vitro and in vivo anti-tumor effects, when combined with ultrasonic irradiation, on androgen-independent prostate cancer (AIPC). Materials and methods Nanobubbles carrying AR siRNA were prepared using poly-L-lysine and electrostatic adsorption methods. Using C4-2 cell activity as a testing index, the optimal irradiation parameters (including the nanobubble number/cell number ratio, mechanical index [MI], and irradiation time) were determined and used for transfection of three human prostate cancer cell lines (C4-2, LNCaP, and PC-3 cells). The AR expression levels were investigated with RT-PCR and Western blot analysis. Additionally, the effects of the nanobubbles and control microbubbles named SonoVue were assessed via imaging in a C4-2 xenograft model. Finally, the growth and AR expression of seven groups of tumor tissues were assessed using the C4-2 xenograft mouse model. Results The nanobubbles had an average diameter of 609.5±15.6 nm and could effectively bind to AR siRNA. Under the optimized conditions of a nanobubble number/cell number ratio of 100∶1, an MI of 1.2, and an irradiation time of 2 min, the highest transfection rates in C4-2, LNCaP, and PC-3 cells were 67.4%, 74.0%, and 63.96%, respectively. In the C4-2 and LNCaP cells, treatment with these binding nanobubbles plus ultrasonic irradiation significantly inhibited cell growth and resulted in the suppression of AR mRNA and protein expression. Additionally, contrast-enhanced ultrasound showed that the nanobubbles achieved stronger signals than the SonoVue control in the central hypovascular area of the tumors. Finally, the anti-tumor effect of these nanobubbles plus ultrasonic irradiation was most significant in the xenograft tumor model compared with the other groups. Conclusion Nanobubbles carrying AR siRNA could be potentially used as gene vectors in combination with ultrasonic irradiation for the treatment of AIPC.